(untitled) (Journal of Computational Mathematics, 1998)
A splitting iteration method is proposed to compute double X_0-breaking bifurcation points. The method will reduce the computational work and storage, it converges linearly with an adjustable speed. Numerical computation shows the effectiveness of splitting iteration method.